2016
DOI: 10.3329/mh.v4i2.23138
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practice related to Occupational Hazards among Maruti Cement Factory workers in Mirchaiya, Siraha, Nepal

Abstract: The main objective of the study is to find out the knowledge, practice and use of Personal Protective Equipments (PPE) among workers of cement factory limited located at Mirchaiya, Siraha, Nepal. We have tried to identify the various sources of information regarding occupational hazards, frequency of health visit in case of health problems or illness, hygiene practices among factory workers and sociodemographic characteristics like age, sex, marital status, income among the workers of cement factory. This is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 4 publications
3
7
0
Order By: Relevance
“…Present study showed 13.2% of workers have respiratory risk while a similar study conducted in Maruti cement factory, Siraha and Udaypur cement factory showed 39% and 24.1% workers respectively were suffering from any illness (15,16) . But, finding of the Dejen cement factory showed higher prevalence (62.9%) (20) .…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…Present study showed 13.2% of workers have respiratory risk while a similar study conducted in Maruti cement factory, Siraha and Udaypur cement factory showed 39% and 24.1% workers respectively were suffering from any illness (15,16) . But, finding of the Dejen cement factory showed higher prevalence (62.9%) (20) .…”
Section: Discussionsupporting
confidence: 61%
“…In the Maruti cement factory, 98% had knowledge of the benefits of PPE while in this study 86% and 83.5% told disease prevention and accident prevention as benefits of PPE. Similarly, 90% of workers have received training while only 70.3% received training on occupational health and safety in the present study (15) . Among total study participants, 87.7% use PPE in this study while only 79% used in Udaypur cement factory (16) and 31.2% used in cement factory of Ethiopia (20) , 96% used in Maruti cement factory (15) and 99% of the workers used PPE as per the study of Aliae Mohamed Hussain (27) .…”
Section: Discussionsupporting
confidence: 46%
See 3 more Smart Citations